STUDI KOMPARATIF: TARI LAWEUT PADA MASYARAKAT PIDIE DAN LHOKSEUMAWE - PUTRI SINAL SURBAKTI (Gesture: Jurnal Seni Tari, 2013)
This research aims to know comparison of the Laweut dancePidie and Lhokseumawe. The sample in this study was a dancer and artist who knew a lot about Laweutdance and art Aceh, located in Pidie and Lhokseumawe. Location of the research conducted in the districts of PidiesubdistrictSigli and the city of LhokseumawesubdistrictLilawangsa, precisely in  PusakaNanggroePidie dance studio and Lhokseumawe in GentaSeuramoedance studio. Time in this research were conducted from July to August. The method used in this research is descriptive qualitative method, which gives a picture, description, information, about a situation that is going on based on the facts. Data was collected through field observations, interviews with several speakers who are competent to problem the study and recording (video and audio-visual). After research it can be seen from the comparison of Laweut dancePidie and Lhokseumawe. Similarities and differences that exist of the form of presentation, especially of motion. Motion is in Pidie dominant on finger picking motion (ketrepjaroe) and the dominant motion from Lhokseumawe area is clap hands, his verse also have many differences. Structural equation lies only in the round Laweut dance, saleuem, likok, saman, kisah, and extracts or lanie. Knowing how the origins of Laweutdance influx of Pidie which is the beginning of the Laweutdance created and grown up to Lhokseumawe. The development of Laweutdance Pidie to Lhokseumawe because people who migrate or seek new life to Lhokseumawe bring all the traditions or culture then develop in Lhokseumawearea and adapt in the area and eventually bring a new form of dance that is seen that this isLhokseumawe’sLaweut that will distinguish the area through the development of the original motion, poetry, pattern, costumes and so on. Keywords:Laweut Dance, Pidie and Lhokseumawe Society, Comparative Study Laweut Dance